Предмет: Алгебра,
автор: Aka2121
3(2x-1)-5(x-3)+6(3x-4) решите пожалуйста
Ответы
Автор ответа:
7
Ответ: 5,7
Объяснение: 3*(2x-1)-5*(x-3)+6*(3x-4)=83+5(x-3)
6х-3-5х+15+18х-24=83+5х-15
19х-12=68+5х
19х-5х=68+12
14х=80
х=80/14
х=5,7
Автор ответа:
5
Ответ:
-12/19
Объяснение:
6x-3-5x+15+18x-24=0
19x=-12
x=-12/19
Похожие вопросы
Предмет: Алгебра,
автор: Аноним
Предмет: Английский язык,
автор: pon0s0
Предмет: Геометрия,
автор: xudkd
Предмет: Математика,
автор: nina858585
Предмет: Математика,
автор: nekitbalagurov